2015
DOI: 10.1039/c5dt01569c
|View full text |Cite
|
Sign up to set email alerts
|

A family of Fe3+based double-stranded helicates showing a magnetocaloric effect, and Rhodamine B dye and DNA binding activities

Abstract: Herein, the synthesis, structural characterization, magnetic properties and guest binding activities of four Fe(3+) based double-stranded helicates namely; [Fe2(L)2](ClO4)(Cl)·4(CH3OH)·2(H2O) (), [Fe2(L)2](BF4)2·2(H2O) (), [Fe2(L)2](NO3)2·3(CH3OH)·2(H2O) (), and [Fe2(L)2](Cl)2·2(CH3OH)·4(H2O) () are reported. Complexes have been synthesized using the hydrazide-based ligand H2L (H2L = N'1,N'4-bis(2-hydroxybenzylidene)succinohydrazide) and the corresponding Fe(2+) salts. Each of the independent cationic complexe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(11 citation statements)
references
References 112 publications
0
11
0
Order By: Relevance
“…Previous reports of 3d‐metal‐based molecular magnetic refrigerants are mainly discrete clusters,30–35 but rare examples of 3d‐metal‐based multidimensional CPs have been documented;26b–d,36–38 moreover, to our best knowledge, there are only three cases of 3d‐metal‐cluster‐based extended structures (Table ) 36–38…”
Section: Recent Advances In Coordination‐cluster‐based Molecular Magnmentioning
confidence: 94%
See 1 more Smart Citation
“…Previous reports of 3d‐metal‐based molecular magnetic refrigerants are mainly discrete clusters,30–35 but rare examples of 3d‐metal‐based multidimensional CPs have been documented;26b–d,36–38 moreover, to our best knowledge, there are only three cases of 3d‐metal‐cluster‐based extended structures (Table ) 36–38…”
Section: Recent Advances In Coordination‐cluster‐based Molecular Magnmentioning
confidence: 94%
“…Furthermore, the target molecular refrigerants cover various structural types, including discrete clusters and cluster‐based 1D, 2D, and 3D extended structures. Herein, we mainly summarize recent progress in the structures and magnetocaloric properties of cluster‐based molecular magnetic refrigerants, in which isolated mononuclear CPs and extended structures constructed from isolated monomers and linkers are not included in the following descriptions 25–28…”
Section: Recent Advances In Coordination‐cluster‐based Molecular Magnmentioning
confidence: 99%
“…It is observed that in high salt concentrations the binding of RB to the DNA phosphate backbone decreases and the binding constant decreases moderately. 34 In addition, the binding of RB to the minor groove of DNA was further indicated by circular dichroism, fluorescence quenching, and molecular docking studies. 25,34 On addition of 100µl of AOLE (stock: 5g/15ml), a further reduction in RB fluorescence intensity was seen due to the interaction between free unbound RB and AOLE as mentioned above.…”
Section: Fluorometric Findingsmentioning
confidence: 99%
“…34 In addition, the binding of RB to the minor groove of DNA was further indicated by circular dichroism, fluorescence quenching, and molecular docking studies. 25,34 On addition of 100µl of AOLE (stock: 5g/15ml), a further reduction in RB fluorescence intensity was seen due to the interaction between free unbound RB and AOLE as mentioned above. The inset of Figure 2 shows differences in the fluorescence intensities of system A and system B. Fluorescence intensity of the system B is higher than that of the system A because the AOLE did not allow the RB to interact with the ct-DNA and more free (unbound) RB is exposed to the excitation light and then produces more emission fluorescence light.…”
Section: Fluorometric Findingsmentioning
confidence: 99%
“…Complexes of metals with salicylidene dihydrazones succin acid dihydrazide exhibit catalytic activity in the oxidation reaction of alkenes [1], are able to bind to DNA [2], and possess antimicrobial activity [3]. Salicyliden dihydrazone dihydrazide succinic acid, like dihydrazone derivatives of other dibasic acids, is potentially hexadentate and 4 anionic, due to deprotonation of two phenolic hydroxyls and two enolic groups, as in structure E. [9], helicate clusters of lanthanides and the influence of anions on their configuration [10] and dimeric and polymer complexes of Sn [11] were also obtained.…”
Section: Introductionmentioning
confidence: 99%